Concept of Peace in Islam Rules and Laws - Ali, Amerah Abdulwhab; Ali, Amerah Abdulwhab (International Journal of Psychosocial Rehabilitation, 2020)
The research is based on studying the concept of peace in Islam by studying the legal rulings related to the concept of peace between Muslims and non-Muslims, and the opinions of jurists in this, in addition to the most important jurisprudence rules related to the concept. About peace. And I reached simple conclusions: The basis of the relationship between Muslims and non-Muslims is the relationship of advocacy and guidance, and that the Islamic call is a universal call, not a regional or racial call.